Skin Manifestations of Personal Protection Devices and Sanitizers Among COVID-19 Healthcare Providers: A Survey at Southern Region Hospitals, Saudi Arabia: Life Sciences-Health - Alfahaad, Hamad Ayed; Ali Alfataih, Mahdi Turki Bin; Al Adainan, Bader Maiedh Mohsen; Al Dundur, Alhassan Ahmed M; Alyami, Ali Mahdi J; Alyami, Ali Hadi M; Almunajjim, Mana Mahdi R; Al Khamsan, Hamad Mahdi K; Al Abbas, Ali Mansour Z; Balhareth, Rashed Saleh M; Alyami, Batool Hamad Hussain; Alzabin, Aljoharah Ali H (International Journal of Life Science and Pharma Research, 2022)
Frontline worker’s prevalence of occupational skin disease has increased as a result of staff infection control measures such increased personal protective equipment (PPE) and stricter hand hygiene procedures. During the COVID-19 pandemic, assess the frequency of occupational skin disorders among healthcare workers at the general hospitals in the Najran region of southern Saudi Arabia is our main aim. Our objective comprises a cross-sectional study that will be carried out at the general hospitals in the Najran region of southern Saudi Arabia between March 1 and April 31, 2022, in order to achieve the goal. All medical professionals received a self-administered online survey (physicians, nurses and paramedics). The questionnaire asked about the severity of skin damage and the frequency and length of time that various infection prevention strategies were used. It was found that 68.2% had new onset of obvious skin damage and 31.8 % did not. 21.6% of the new onset of obvious skin damage was on the fingertips, 46.6% was on the hands, 22.4% was in paws, 3.4% was on the face and 6.0% was under the eye. 29.8% of the symptoms of the damaged site was itching, 44.7% dryness, 12.8% burning/pain, and 12.8% tenderness. 16.5 % of the type of skin lesions was peeling, 28.2% fissure, 18.8% erosion/ulcer, 24.7% redness, 4.7% papule (pimples) and 7.1% others. In our study, 68.2% of our participants suffered obvious skin damage during the pandemic: 90.6% of this occurred on the hands and 9.4% on the face. Contact dermatitis in the form of itching, dryness, burning, pain and tenderness were the most common adverse effects noted. Therefore, it is important to organize training on the prevention and management of possible skin lesions due to PPE use according to guidelines.